ANALISIS PENGARUH KUALITAS PRODUK, CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN PERPINDAHAN MEREK SEPEDA MOTOR MATIC YAMAHA KE HONDA (Studi Kasus pada Masyarakat Kota Semarang) - Assiddiq, Ferdian; Sutopo, Sutopo (Diponegoro Journal of Management, 2015)
Total sales of Yamaha motorcycles between 2012 and 2014 decreased , on the other hand Honda has increased , in which the other motor brands tend to stagnate . Among the several factors that led to the transfer of the brand Yamaha to Honda allegedly due to product quality , brand image and price .             Thus , this study aims to analyze: 1 ) the influence of the quality of the product on a Yamaha motorcycle brand switching to Honda ; 2 ) the effect on the consumer response to the brand image brand switching to Honda Yamaha motorcycle ; and 3 ) the effect of price on a Yamaha. Intake sample size ( sample size) using the formula Widiyanto (2008 ) , so the number of respondents found 100 people. So as to produce the regression equation is as follows    : Y = 0,436 X1 + 0,279 X2 + 0,220 X3            Sampling technique using purposive sampling , where researchers focused on respondents who had previously been using the Yamaha brand and brand switching to Honda . Deployment region of respondents in Semarang includes four (4 ) villages , namely : Banyumanik , Tembalang , Srondol , Gajahmungkur .motorcycle brand switching to Honda